KONSTRUKSI HUKUM PERJANJIAN KERJASAMA PENJUALAN PRODUK DIGITAL ANTARA PT XYZ DENGAN PT ABC Sdn. Bhd. DENGAN SISTEM MULTILEVEL MARKETING - Legita Tandanu; Ariawan Gunadi (Fakultas Hukum Universitas Kristen Indonesia, 2020)
As a result of the influence of world globalization, with the rapid development of international relations and the development of information technology, the need to know about the law of other legal systems in the world is increasingly felt high so that lately the development of knowledge about comparative law is very fast. That is what is felt closely related to PT XYZ with PT ABC Sdn. Bhd. in Malaysia. So that in the end raises the problem of how the legal construction of digital product sales cooperation agreements with the Multi-Level Marketing (MLM) system between the two companies and what the implementation of the partnership between the two companies is like. Therefore, the purpose of the problem is to find out and describe in detail the model of the digital product sales agreement with the MLM system and how the implementation of the cooperation agreement should be carried out in the perspective of rules in Indonesia and Malaysia. If the existing law does not explicitly determine the cancellation of the prohibited agreement, it is not necessary and will be confusing to find the cause of the cancellation of the agreement (because of the prohibited cause). The agreement was canceled not based on the provisions of Article 1335 and 1337 of the Indonesian Criminal Code, but on the basis of the provisions of the law which stated it. The cause of the agreement is the purpose of the agreement made by the parties. However, it cannot be said that if the parties enter into an agreement means the purpose of the parties is to do the action (which is without a false or prohibited cause).